Tata Tertib Busana Kampus: Edukasi, Etika dan Komunikasi - Hayati, Afita Nur (Dinamika Ilmu, 2013)
Education as consciuos process have prime goals, help youngers be smart and help them have morality. Therefore, they must study about ethics, a science that learn about bad and good manner as long as peopleâs knows through communications, a fundamental instrument to sharing meaning in order to have similarity namely religious culture.